Higher-Order Thinking Skills in Music Education: A Comprehensive Analysis - Pu, Jiarui; Safian, Abdul Rahman Bin; Nasrifan, Mohd Nizam Bin (Grenek: Jurnal Seni Musik, 2024)
Researchers have continued to urge the importance of strengthening students' higher-order thinking skills (HOTS) as a key factor for education. Researchers in the field of music education are actively advocating for the enhancement of HOTS among students. To advance research in this area, a thorough and comprehensive literature review is necessary. This review synthesized existing findings to elucidate how HOTS can enhance musical education and performance and offer insights into effective pedagogical strategies. By systematically examining the integration of HOTS in musical contexts, pointing out gaps in research, the study contributed to advancing educational practices and theoretical understanding in this domain. Furthermore, offers insights that can inform the development of future research on HOTS in music teaching and learning.